Thermoelectric Power in Nanostructured Materials Strong Magnetic Fields - Ghatak, Kamakhya Prasad; Bhattacharya, Sitangshu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This is the first monograph which solely investigates the thermoelectric power in nanostructured materials under strong magnetic field (TPSM) in quantum confined nonlinear optical, III-V, II-VI, n-GaP, n-Ge, Te, Graphite, PtSb2, zerogap, II-V, Gallium Antimonide, stressed materials, Bismuth, IV-VI, lead germanium telluride, Zinc and Cadmium diphosphides, Bi2Te3, Antimony and carbon nanotubes, III-V, II-VI, IV-VI and HgTe/CdTe superlattices with graded interfaces and effective mass superlattices under magnetic quantization, the quantum wires and dots of the aforementioned superlattices by formulating the appropriate respective carrier energy spectra which in turn control the quantum processes in quantum effect devices. The TPSM in macro, quantum wire and quantum dot superlattices of optoelectronic materials in the presence of external photo-excitation have also been studied on the basis of newly formulated electron dispersion laws. This monograph contains 150 open research problems which form the very core and are useful for Ph. D students and researchers in the fields of materials science, solid state sciences, computational and theoretical nanoscience and technology, nanostructured thermodynamics and condensed matter physics in general in addition to the graduate courses on modern thermoelectric materials in various academic departments of many institutes and Universities. The book is written for researchers and engineers, post graduate students, professionals in the fields of materials science, nanoscience and technology, solid state sciences, nanostructured thermodynamics and condensed matter physics.
Thermoelectric power under large magnetic field in quantum confined materials -- Thermoelectric Power in Quantum Dots Under Large Magnetic Field -- Thermoelectric Power in Ultrathin Films and Quantum Wires Under Large Magnetic Field -- Thermoelectric Power in Quantum Dot Superlattices Under Large Magnetic Field -- Thermoelectric Power in Quantum Wire Superlattices Under Large Magnetic Field -- Thermoelectric power under magnetic quantization in macro and micro electronic materials -- Thermoelectric Power in Macroelectronic Materials Under Magnetic Quantization -- Thermoelectric Power in Superlattices Under Magnetic Quantization -- Thermoelectric Power in Ultrathin Films Under Magnetic Quantization -- Thermoelectric power under large magnetic field in quantum confined optoelectronic materials in the presence of light waves -- Optothermoelectric Power in Ultrathin Films and Quantum Wires of Optoelectronic Materials Under Large Magnetic Field -- Optothermoelectric Power in Quantum Dots of Optoelectronic Materials Under Large Magnetic Field -- Optothermoelectric Power in Quantum-Confined Semiconductor Superlattices of Optoelectronic Materials Under Large Magnetic Field -- Thermoelectric power under magnetic quantization in macro and micro optoelectronic materials in the presence of light waves -- Optothermoelectric Power in Macro-Optoelectronic Materials Under Magnetic Quantization -- Optothermoelectric Power in Ultrathin Films of Optoelectronic Materials Under Magnetic Quantization -- Optothermoelectric Power in Superlattices of Optoelectronic Materials Under Magnetic Quantization -- Applications and Brief Review of Experimental Results -- Conclusion and Future Research.
Keywords: Magnetism; Engineering; Nanotechnology; Materials; Materials Science; Nanotechnology; Magnetism, Magnetic Materials; Nanotechnology and Microengineering; Ceramics, Glass, Composites, Natural Methods; Metallic Materials